Optimal. Leaf size=18 \[ e^{\frac {1}{6+e-x-e^{e^2} x}} \]
________________________________________________________________________________________
Rubi [A] time = 0.29, antiderivative size = 17, normalized size of antiderivative = 0.94, number of steps used = 4, number of rules used = 4, integrand size = 77, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.052, Rules used = {6, 12, 6688, 2209} \begin {gather*} e^{\frac {1}{-\left (\left (1+e^{e^2}\right ) x\right )+e+6}} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 6
Rule 12
Rule 2209
Rule 6688
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {e^{-\frac {1}{-6-e+x+e^{e^2} x}} \left (1+e^{e^2}\right )}{36+e^2+e (12-2 x)-12 x+\left (1+e^{2 e^2}\right ) x^2+e^{e^2} \left (-12 x-2 e x+2 x^2\right )} \, dx\\ &=\left (1+e^{e^2}\right ) \int \frac {e^{-\frac {1}{-6-e+x+e^{e^2} x}}}{36+e^2+e (12-2 x)-12 x+\left (1+e^{2 e^2}\right ) x^2+e^{e^2} \left (-12 x-2 e x+2 x^2\right )} \, dx\\ &=\left (1+e^{e^2}\right ) \int \frac {e^{\frac {1}{6+e-\left (1+e^{e^2}\right ) x}}}{\left (6+e-\left (1+e^{e^2}\right ) x\right )^2} \, dx\\ &=e^{\frac {1}{6+e-\left (1+e^{e^2}\right ) x}}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.07, size = 18, normalized size = 1.00 \begin {gather*} e^{\frac {1}{6+e-x-e^{e^2} x}} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.71, size = 17, normalized size = 0.94 \begin {gather*} e^{\left (-\frac {1}{x e^{\left (e^{2}\right )} + x - e - 6}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.89, size = 39, normalized size = 2.17 \begin {gather*} \frac {{\left (e^{\left (e^{2}\right )} + 1\right )}^{2} e^{\left (-\frac {1}{x e^{\left (e^{2}\right )} + x - e - 6}\right )}}{e^{\left (2 \, e^{2}\right )} + 2 \, e^{\left (e^{2}\right )} + 1} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.49, size = 17, normalized size = 0.94
method | result | size |
gosper | \({\mathrm e}^{\frac {1}{{\mathrm e}-x +6-x \,{\mathrm e}^{{\mathrm e}^{2}}}}\) | \(17\) |
risch | \({\mathrm e}^{\frac {1}{{\mathrm e}-x +6-x \,{\mathrm e}^{{\mathrm e}^{2}}}}\) | \(17\) |
derivativedivides | \(-\frac {\left (1+{\mathrm e}^{{\mathrm e}^{2}}\right ) {\mathrm e}^{\frac {1}{{\mathrm e}-x +6-x \,{\mathrm e}^{{\mathrm e}^{2}}}}}{-1-{\mathrm e}^{{\mathrm e}^{2}}}\) | \(33\) |
default | \(-\frac {\left (1+{\mathrm e}^{{\mathrm e}^{2}}\right ) {\mathrm e}^{\frac {1}{{\mathrm e}-x +6-x \,{\mathrm e}^{{\mathrm e}^{2}}}}}{-1-{\mathrm e}^{{\mathrm e}^{2}}}\) | \(33\) |
norman | \(\frac {\left ({\mathrm e}+6\right ) {\mathrm e}^{-\frac {1}{x \,{\mathrm e}^{{\mathrm e}^{2}}-{\mathrm e}+x -6}}+\left (-1-{\mathrm e}^{{\mathrm e}^{2}}\right ) x \,{\mathrm e}^{-\frac {1}{x \,{\mathrm e}^{{\mathrm e}^{2}}-{\mathrm e}+x -6}}}{{\mathrm e}-x +6-x \,{\mathrm e}^{{\mathrm e}^{2}}}\) | \(66\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.36, size = 18, normalized size = 1.00 \begin {gather*} e^{\left (-\frac {1}{x {\left (e^{\left (e^{2}\right )} + 1\right )} - e - 6}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 2.08, size = 15, normalized size = 0.83 \begin {gather*} {\mathrm {e}}^{\frac {1}{\mathrm {e}-x\,\left ({\mathrm {e}}^{{\mathrm {e}}^2}+1\right )+6}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.51, size = 17, normalized size = 0.94 \begin {gather*} e^{- \frac {1}{x + x e^{e^{2}} - 6 - e}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________